Healthy but not osteoarthritic human meniscus-derived matrix scaffolds promote meniscus repair - Firoozi, Saman; Ley, Jon C.; Chasse, Dawn A. D.; Attarian, David E.; Wellman, Samuel S.; Amendola, Annunziato; McNulty, Amy L. (Frontiers in Bioengineering and Biotechnology, 2024)
Meniscus tissue is commonly injured due to sports-related injuries and age-related degeneration and approximately 50% of individuals with a meniscus tear will develop osteoarthritis (OA). Given that the meniscus has limited healing potential, new therapeutic strategies are required to enhance meniscus repair. Porcine meniscus-derived matrix (MDM) scaffolds improve meniscus integrative repair, but sources of human meniscus tissue have not been investigated. Therefore, the objectives of this study were to generate healthy and osteoarthritic (OA) MDM scaffolds and to compare meniscus cellular responses and integrative repair. Meniscus cells showed high viability on both healthy and OA scaffolds. While DNA content was higher in cell-seeded OA scaffolds than cell-seeded healthy scaffolds, CCK-8, and both sGAG and collagen content were similar between scaffold types. After 28 days in an ex vivo meniscus defect model, healthy and OA scaffolds had similar DNA, sGAG, and collagen content. However, the shear strength of repair was reduced in defects containing OA scaffolds compared to healthy scaffolds. In conclusion, healthy human allograft tissue is a more useful source for generating MDM scaffolds that can support cellular growth, ECM production, and ex vivo integrative repair of the meniscus, highlighting the potential suitability for tissue engineering approaches to improve meniscus repair.